Adsorption and experiment design for the environmentally friendly manufacture of copper oxide nanoparticles from olive leaf extraction (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The creation of CuO nanoparticles have been used olive leaf extraction is focus of the work. Scanning electron microscopy (SEM) revealed that the green-produced copper oxide nanoparticles were spherical, with a mean particle size of 74 nm. CuO nanoparticles were seen in their crystalline and monoclinic phases on the XRD graph. The DebyeScherrer formula showed that 80 nm was the average crystal size. Using crystal violet, the nano-adsorbents' adsorption properties were investigated, and the adsorption performance at room temperature was 87 mg/g. At pH 4, crystal violet dye is most successfully adsorb able by CuO NPs, Upon adding the CV in concentrations of 0.06 g/0.05 L. Absorption was utilized to optimize a number of process variables, including pH solution (X1: 2 - 11), adsorbing dose (X2: 0.01 - 0.08 g/L), and [CV] dye concentration (X3: 10 - 80 mg/L). The chosen Response surface methodology (RSM) was successful in optimizing the decolorization conditions of CV, as shown by the adjusted coefficient of determination (R2) value of 0.99, which also showed that the utilized model was highly appropriate.